Detection of Liver Steatosis With a Novel Ultrasound-Based Technique: A Pilot Study Using MRI-Derived Proton Density Fat Fraction as the Gold Standard. Issue 10 (October 2019) - Ferraioli, Giovanna; Maiocchi, Laura; Raciti, Maria Vittoria; Tinelli, Carmine; De Silvestri, Annalisa; Nichetti, Mara; De Cata, Pasquale; Rondanelli, Mariangela; Chiovato, Luca; Calliada, Fabrizio; Filice, Carlo
Abstract : OBJECTIVES: The primary aim of this study was to investigate the value of attenuation imaging (ATI), a novel ultrasound technique for detection of steatosis, by comparing the results to that obtained with controlled attenuation parameter (CAP) and by using MRI-derived proton density fat fraction (PDFF) as reference standard. METHODS: From March to November 2018, 114 consecutive adult subjects potentially at risk of steatosis and 15 healthy controls were enrolled. Each subject underwent ATI and CAP assessment on the same day. MRI-PDFF was performed within a week. RESULTS: The prevalence of steatosis, as defined by MRI-PDFF ≥ 5%, was 70.7%. There was a high correlation of ATI with MRI-PDFF (r = 0.81, P < 0.0001). The correlation of CAP with MRI-PDFF and with ATI, respectively, was moderate (r = 0.65, P < 0.0001 and r = 0.61, P < 0.0001). The correlation of ATI or CAP with PDFF was not affected by age, gender, or body mass index. Area under the receiver operating characteristics of ATI and CAP, respectively, were 0.91 (0.84–0.95; P < 0.0001) and 0.85 (0.77–0.91; P < 0.0001) for detecting S > 0 steatosis (MRI-PDFF ≥ 5%); 0.95 (0.89–0.98; P < 0.0001) and 0.88 (0.81–0.93; P < 0.0001) for detecting S > 1 steatosis (MRI-PDFF ≥ 16.3%). The cutoffs of ATI and CAP, respectively, were 0.63 dB/cm/MHz and 258 dB/m for detecting S > 0 liver steatosis; 0.72 dB/cm/MHz and 304 dB/m for detecting S > 1 steatosis. ATI performed better than CAP, and this improvement was statistically significant for S > 1 ( P = 0.04). DISCUSSION: This study shows that, in patients with no fibrosis/mild fibrosis, ATI is a very promising tool for the noninvasive assessment of steatosis.